INTERNAL VERSUS EXTERNAL LOCUS OF CONTROL AMONG STUDENTS IN TERTIARY EDUCATIONAL INSTITUTIONS: A REVIEW OF RELATED LITERATURE AND IMPLICATIONS FOR EDUCATIONAL PSYCHOLOGY - Gatawa, Mudassir Ibrahim; Yusuf, Ibrahim (Sokoto Educational Review, 2015)
This paper examined issues related to the search for means of improving performance among learners through explaining one of the psychological basis of academic achievement, that is, Locus of Control (LOC) which is a personality variable. The concept and different orientations of LOC were discussed. The issue of age, familial origins and gender with relevance to LOC were discussed. The desirability or otherwise of the internal and external LOC was also discussed. The paper concluded that higher external orientation and higher internal orientation could lead to anxiety and frustration in some instances. Implications for Educational Psychology were raised, which included counselling students to realize their mistakes, so that they don’t attribute their expected failures to the teacher or something else. They should also be counselled not to set unachievable goals that when effort put in place failed, the situation would not result into anxiety and frustration.